Pengaruh Variasi Bahan Aditif Pada Base Quench Medium dan Holding Time Tempering Terhadap Sifat Mekanik Material Roda Gigi - Alexander David Kurniawan; Udianto, Pondi (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Gears are one of the most important components in various machine systems, and in their use, the gears rub and press against each other with other components, so they often experience wear on their surfaces. Therefore, to overcome these problems, the gear material is given a hardening and tempering heat treatment to improve its mechanical properties. The purpose of this study was to determine the effect of variations in cooling media in the quenching process and tempering holding time on the hardness value and impact strength of S45C steel. The method used is S45C steel heated at 950°C for 35 minutes, then cooled using water + 0.12% activated carbon, a 5% NaCl solution, and SAE 15 W 40 oil + 0.12% activated carbon. After that, it was tempered at 260 °C for 15 minutes, 25 minutes, and 35 minutes. Then a hardness test was carried out to determine the hardness value, and an impact test was carried out to determine the toughness value. From the results of the study, it was found that the optimum parameters for overcoming wear problems on gears were using water + 0.12% activated carbon cooling media and a tempering holding time of 15 minutes. From these optimum parameters, it produces a high hardness value of 36.3 HRC and an impact price of 0.23 J/mm².